Biochemical Contents of Nutritional Values of Clarias batrachus - Thorat MM (International Journal of Life Sciences, 2017)
The Biochemical contents like minerals & vitamins were studied in clarias batrachus. Minerals constitute 1 to 2 % fish flesh content. The bulk is concentrated in fish bones, muscles & scales. Vitamins A, B & D provides fish, Liver is particularly rich in vit B12 & B-complex.Fish flesh content proteins, moisture, minerals & other constituents. The water content of the fish known to vary inversely as the fat content, other constituents do not vary widely. Vitamins & enzymes are also present.